The Implementation of Government Regulation Number 53 Year 2010 Concerning Discipline of Civil Servants in Bener Meriah Regency 2019 in the Education Personnel Board And Bener Meriah District Training - Susi Sri Yuliarti; Muhammad Bin Abubakar; Rasyidin Rasyidin (Master Program of Sociology, Universitas Malikussaleh,, 2020)
This study examines the implementation of Government Regulation No. 53/2010 concerning Civil Servant Discipline. The research objective is to understand how compliance and barriers to civil servants are in implementing these policies. The theoretical perspective used is the theory of public policy implementation according to Anderson. The research method used is a qualitative research method. The results of the study show that the compliance of civil servants in Bener Meriah Regency in 2019 in implementing Government Regulation Number 53 of 2020 concerning Civil Servant Discipline is still not effectively implemented, both in terms of actors implementing policies, the nature of the administrative process, compliance, and the impact of policies. which is implemented. Internal obstacles are caused by the inadequacy of the BKPP Bener Meriah Regency in supervising and evaluating civil servants who violate disciplinary rules, and the low awareness of civil servants in implementing discipline in duty, which is also influenced by the low reward or appreciation for civil servants who have high discipline and lack of discipline. he stressed that the punishment was given to civil servants who had low discipline by the leadership of the SKPK. External obstacles are caused by the lack of decisiveness and lack of supervision from SKPK leaders in following up on civil servants who violate discipline.